Perancangan Aplikasi "SHOLAT YUKK" Pada Android Sebagai Media Pembelajaran Ibadah Shalat Anak-Anak - Hendy Cahya Lesmana; Rizal Isnanto; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2016)
The implementation of the five times obligatory prayers a day is mandatory for Muslims. To inculcate the habit of five times praying a day should begin at the early age. Less fortunate, there are only limited media used for practicing the five times prayer that is attractive for children. It requires an innovative, interesting, and easier learning method with the use of technology in Islam especially learning the procedure of the five times a day obligatory prayers. Given the number of smartphones users with the Android operating system, so a "SHOLAT YUKK" software application is made On Android for children’s Learning Media Prayer. The results of this research are the realization of learning application procedures for the five daily prayers based on Android that is used for the five-day prayers learning, especially for children. This "SHOLAT YUKK" software applications on Android as a prayers learning for children can now be used as an obligatory five times a day prayers learning.